Social cognition in patients with acquired brain lesions: An overview on an under-reported problem. Issue 3 (4th May 2022) - Maggio, Maria Grazia; Maresca, Giuseppa; Stagnitti, Maria Chiara; Anchesi, Smeralda; Casella, Carmela; Pajno, Valentina; De Luca, Rosaria; Manuli, Alfredo; Calabrò, Rocco Salvatore
Abstract: Social cognition (SC) consists of mental representations of interpersonal relationships, which are used flexibly by the individual to promote functional social behaviors and achieve the goals. SC is a multidimensional construct and is supported by the activity of distributed neural networks in which different cortical and subcortical regions of the brain are involved. The review aims to evaluate the current literature on SC taking into account how it is compromised in acquired brain injury. Studies performed between 2010 and 2019 and fulfilling the selected criteria were searched on PubMed, Scopus, Cochrane and Web of Sciences databases. Impairment of SC is a neglected but common consequence of ABI, often leading to disordered interpersonal functioning and poor regulation of personal behavior with impaired social adaptation and quality of life of both the patient and his/her family. This review supports the idea that SC could have an important role in the management of neurological patients by both clinicians and caregivers.